Promising Direction: Use Of Insects As Raw Material For Chitosan Production (Texas Journal of Agriculture and Biological Sciences, 2026)
The article examines the possibility of using insects as an alternative source of chitosan. The chemical composition of insect exoskeletons, the main stages of the technological process for obtaining chitosan, and the advantages of this raw material in terms of sustainable development are described. It has been shown that insects can be considered as a promising and environmentally safe raw material base for the production of chitosan. Chitosan is a natural biopolymer with high biological activity and a wide range of practical applications